2020
DOI: 10.1021/acsami.0c11103
|View full text |Cite
|
Sign up to set email alerts
|

Unclonable Perovskite Fluorescent Dots with Fingerprint Pattern for Multilevel Anticounterfeiting

Abstract: Anticounterfeiting techniques based on physical unclonable functions exhibit great potential in security protection of extensive commodities from daily necessities to high-end products. Herein, we propose a facile strategy to fabricate an unclonable super micro fingerprint (SMFP) array by introducing in situ grown perovskite crystals for multilevel anticounterfeiting labels. The unclonable features are formed on the basis of the differential transportation of a microscale perovskite precursor droplet during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 34 publications
(59 reference statements)
1
68
0
1
Order By: Relevance
“…[24] Liu et al proposed a facile strategy to fabricate an unclonable super micro fingerprint array by introducing in situ grown perovskite crystals for multilevel anti-counterfeiting labels. [10] Yu et al demonstrated the potential applications of hydrochromic CsPbBr 3 NCs in anti-counterfeiting by using CsPbBr 3 NCs@ mesoporous silica nanospheres as the starting material. [25] In this paper, we introduce an unclonable anti-counterfeiting technique with high-throughput and low-cost preparation and convenient, rapid, and repeatable verification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Liu et al proposed a facile strategy to fabricate an unclonable super micro fingerprint array by introducing in situ grown perovskite crystals for multilevel anti-counterfeiting labels. [10] Yu et al demonstrated the potential applications of hydrochromic CsPbBr 3 NCs in anti-counterfeiting by using CsPbBr 3 NCs@ mesoporous silica nanospheres as the starting material. [25] In this paper, we introduce an unclonable anti-counterfeiting technique with high-throughput and low-cost preparation and convenient, rapid, and repeatable verification.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Anti-counterfeiting labels with physical unclonable functions (PUF) are a feasible solution to the above shortcomings. Since the introduction of the PUF in 2002, [7] many anticounterfeiting labels with different PUF characteristics have been developed, such as unique bionic fingerprint pattern with random surface topography; [8][9][10] randomly distributed nanoparticle pattern, including flower-like patterns with random pinning points, [11] nanowires coated with fluorescent dyes in random positions, [12] etc. In addition, researchers have prepared many types of PUF anticounterfeiting labels with optical response.…”
mentioning
confidence: 99%
“…Another is “non‐fluorescent” ink, which is produced by dissolving raw materials of PQDs in a solvent to form transparent precursor solutions. [ 27,28 ] After printing the ink on the substrate, in situ crystallization of patterned PQD CCFs occurs as the solvent evaporates. For instance, Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6–10 ] According to the previous reports, the global economic losses caused by counterfeiting may reach to 1.82 trillion USD in 2020. [ 11 ] Therefore, developing powerful anti‐counterfeiting technologies is highly demanded.…”
Section: Introductionmentioning
confidence: 99%